Establishing Research Legitimacy in the Contested Political Ground of Contemporary Northern Ireland - Knox, Colin (Qualitative Research, 2001)
Despite the plethora of literature on the macro politics of Northern Ireland, there is a dearth of material on grassroots activity, in particular the dynamic between communities and paramilitary groups which enforce ‘law and order’ in working class areas. Political progress in the form of the Belfast Agreement (1998) has overshadowed the ongoing level of violence at the micro level and the voice of victims remains unheard in the search to attain a greater goal – a long-term political and constitutional settlement. This paper examines the methodological difficulties in establishing research legitimacy in the contested political arenas of Northern Ireland. It considers issues of access, establishing the researchers’ bona fides, openness and transparency, language and personal security, and offers some insights into research in sensitive topics
Keywords: Northern Ireland; Legitimacy